Erubescensoic Acid, a new polyketide and a xanthonopyrone SPF-3059-26 From the culture of the marine sponge-associated fungus penicillium erubescens KUFA 0220 and Antibacterial activity evaluation of some of its constituents - Kumla, D (2019)
A new polyketide erubescensoic acid (1), and the previously reported xanthonopyrone, SPF-3059-26 (2), were isolated from the uninvestigated fractions of the ethyl acetate crude extract of the marine sponge-associated fungus Penicillium erubescens KUFA0220. The structures of the new compound, erubescensoic acid (1), and the previously reported SPF-3059-26 (2), were elucidated by extensive analysis of 1D and 2D-NMR spectra as well as HRMS. The absolute configuration of the stereogenic carbon of erubescensoic acid (1) was determined by X-ray analysis. Erubescensoic acid (1) and SPF-3059-26 (2), together with erubescenschromone B (3), penialidin D (4), and 7-hydroxy-6-methoxy-4-oxo-3-[(1E)-3-oxobut-1-en-1-yl]-4H-chromen-5-carboxylic acid (5), recently isolated from this fungus, were assayed for their antibacterial activity against gram-positive and gram-negative reference strains and the multidrug-resistant (MDR) strains from the environment. The capacity of these compounds to interfere with the bacterial biofilm formation and their potential synergism with clinically relevant antibiotics for the MDR strains were also investigated.